Faktor-Faktor Penentu Nilai Perusahaan: Kinerja Keuangan, Struktur Modal, dan Ukuran pada Sektor Energi di BEI - Parera, Regita; Purwatiningsih, Purwatiningsih (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This research aims to determine and test the influence of financial performance, capital structure and company size on company value in energy sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The population is 76 companies. The sampling method used purposive sampling, 17 companies were obtained with a research period of 5 years so the total research sample was 85. This research uses secondary data sourced from company financial reports as data or research objects. The data analysis techniques used are descriptive statistical analysis and multiple regression analysis. By processing the data using E-views 9 software. The research results show that simultaneously financial performance, capital structure and company size influence company value. Partial testing of financial performance has no effect on company value, capital structure has no effect on company value and company size has no effect on company value.